Simultaneous characterization of cross- and in-plane thermal transport in insulator patterned by directionally aligned nano-channels - Abdullaev, A.; Utegulov, Zhandos N.; Chauhan, Vinay S.; O’Connell, Jacques; Skuratov, Vladimir; Khafizov, M. (AIP Publishing, 2020)
Anisotropic thermal transport behavior was investigated in a single crystal sapphire patterned by vertically aligned few-nanometer diameter and several micrometer long cylindrical ion tracks. These ion tracks were introduced by exposing the sapphire to energetic ions of xenon accelerated to 167 MeV with fluences ranging from 1012 to 1014 ions/cm2. It was found that, in the low ion-track density regime, cross-plane thermal conductivity is larger, whereas in the high track density regime, the trend reverses and in-plane conductivity becomes larger. The crossover between these regimes is attributed to the interplay between phonon scattering with ion track boundaries and phonon confinement effects. In the low track density regime, the material is described by bulk phonon dispersion and anisotropy in thermal transport is attributed to the aligned nature of tracks that effectively reduce the mean free path of phonons traveling in the in-plane direction more than in the cross-plane direction. In the high-density regime, larger conductivity reduction in the cross-plane direction is consistent with previous observations, where the anisotropic reduction in thermal conductivity is owed to the anisotropic reduction of acoustic velocity caused by phonon confinement. Our results are further supported by an analytical model describing phonon mediated thermal transport.